Deep Dive into Digital Transformation in Higher Education Institutions - Mamdouh Alenezi (MDPI AG, 2021)
In the present times, digital transformation has gained momentum. Contemporary higher education institutions have been embracing new technologies and transforming their practices, business models and process. Digital transformation in the higher education institutions is about the development of new more advanced and effective methods and practices in pursuit of the higher education's mission. The present paper links digital transformation and higher education institutions. The paper discusses existing models for the incorporation of digital transformation in higher education institutions. The paper also delineates the challenges faced by higher education institutions in pursuit of digital transformation.